1989
DOI: 10.1136/vr.124.13.329
|View full text |Cite
|
Sign up to set email alerts
|

Detection of feline calicivirus antigens in the joints of infected cats

Abstract: Twelve specific pathogen free cats were used to investigate the role of calicivirus in causing lameness. These were divided into two groups each of six cats; one group of cats had previously been vaccinated, the other had not. Three cats in each group were given live vaccine virus (F9 related) by the subcutaneous route and two in each group were challenged intranasally with field virus (A4), either four or seven days before euthanasia. The other two cats were controls. Virus was isolated from the oropharynx of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…FCV is endemic in most catteries, shelters and large multiple cat households, where up to one-fourth of cats may be orally shedding the virus at any given time (Bennett et al, 1989;Harbour et al, 1991;Dawson et al, 1993a, b). FCV exists in numerous overlapping serotypes but is basically a single species (Gillespie and Scott, 1973).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FCV is endemic in most catteries, shelters and large multiple cat households, where up to one-fourth of cats may be orally shedding the virus at any given time (Bennett et al, 1989;Harbour et al, 1991;Dawson et al, 1993a, b). FCV exists in numerous overlapping serotypes but is basically a single species (Gillespie and Scott, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Pedersen and colleagues (1983) added the feature of`limping' to the FCV disease syndrome. The lameness appears to be associated with acute viremia and localization of virus and/or immune complexes in the joints (Bennett et al, 1989;Dawson et al, 1994). Following recovery from acute disease, up to one-fourth of cats will shed the virus for a prolonged period of time from their oropharynx (Bennett et al, 1989;Harbour et al, 1991;Dawson et al, 1993a, b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feline calicivirus (FCV) is a ubiquitous respiratory and oral pathogen of domestic cats (Gaskell et al, 2004a). Other clinical signs reported include lameness www.elsevier.com/locate/vetmic Veterinary Microbiology 118 (2006) 12-25 (Bennett et al, 1989;Dawson et al, 1994;Pedersen et al, 1983), a recently reported virulent systemic disease (Coyne et al, 2006a;Hurley et al, 2004;Pedersen et al, 2000;Schorr-Evans et al, 2003) and a possible association with chronic stomatitis Thompson et al, 1984). Vaccines against FCV are widely used in the domestic cat population, and although reasonably effective in conferring clinical protection, they do not prevent infection Gaskell et al, 1982Gaskell et al, , 2004bPedersen and Hawkins, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Lameness and chronic oral inflammatory syndromes have been linked to calicivirus infection and vaccination with modified-live calicivirus vaccines. 3 ,7, 10, 11, 45, 57 Risk of exposure to either FHV-1 or FCV is high, because both organisms are widespread tn the feline population.…”
Section: Feline Viral Rhinotracheitis and Feline Calicivirus Infectionmentioning
confidence: 99%